2022
DOI: 10.1111/hel.12936
|View full text |Cite
|
Sign up to set email alerts
|

Current role of tailored therapy in treating Helicobacter pylori infections. A systematic review, meta‐analysis and critical analysis

Abstract: Background and Aims Recent guidelines dictate that all Helicobacter pylori (H. pylori) infected subjects should receive curative therapy. The efficacy of empirical regimens for H. pylori eradication might decline with bacterial, drug, and host factors. The necessity of a tailored therapy still remains controversial. Here we provide a meta‐analysis of the current status of susceptibility‐based (tailored) therapy in which susceptibility‐based therapies were compared to the currently accepted choice of empiric th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…54 While tailoring treatment based on local resistance is important, it must be done consider responsible antibiotic stewardship. 55,56 A belief that the treatment is worse than the symptoms of Hp would influence 70% of all our respondents' decisions to seek care and 81% indicated that knowledge about Hp being a cause of their symptoms and as a cause of GC would affect their willingness to comply with prescribed therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 While tailoring treatment based on local resistance is important, it must be done consider responsible antibiotic stewardship. 55,56 A belief that the treatment is worse than the symptoms of Hp would influence 70% of all our respondents' decisions to seek care and 81% indicated that knowledge about Hp being a cause of their symptoms and as a cause of GC would affect their willingness to comply with prescribed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some previously suggested approaches include pre‐sorted pill packs, extended physician counseling, literature on known/expected side effects in easy‐to‐understand language, and careful follow up to ensure adherence 54 . While tailoring treatment based on local resistance is important, it must be done consider responsible antibiotic stewardship 55,56 …”
Section: Discussionmentioning
confidence: 99%
“…Empirical H. pylori therapies are the most prescribed and are still proposed as first-line options, in parallel to the antibiotic susceptibility-based therapies, by major consensus conferences [ 2 , 16 ]. Despite the fact that antibiotic stewardship is largely becoming important for H. pylori schemes, availability, cost, and convenience prevents its widespread implementation [ 2 , 31 , 32 ]. Moreover, recent meta-analyses show that most susceptibility-guided therapies fail to overcome the acceptable 90% eradication rate, or even do not perform better than the empiric quadruple (with or without bismuth) regimens [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that antibiotic stewardship is largely becoming important for H. pylori schemes, availability, cost, and convenience prevents its widespread implementation [ 2 , 31 , 32 ]. Moreover, recent meta-analyses show that most susceptibility-guided therapies fail to overcome the acceptable 90% eradication rate, or even do not perform better than the empiric quadruple (with or without bismuth) regimens [ 31 , 32 , 33 ]. When bismuth alone or in an all-in-one capsule with antibiotics is available, it is the preferred first choice for empirical therapy [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors arbitrarily attributed their even lesser levofloxacin-based regimen eradication rates to an even more increase in levofloxacin resistance in the Egyptian community after the COVID-19 pandemic (aftermath of levofloxacin misuse in the management of COVID-19) [ 27 ]. However, one should not forget that both eradication treatments underperformed significantly compared to eradication rates of at least 90% as the desired outcome, thereby rendering their findings of low scientific value [ 31 ].…”
Section: Introductionmentioning
confidence: 99%